Pancreas Transplantation from Donors after Circulatory Death: an Irrational Reluctance? - Leemkuil, M. (Curr Diab Rep, 2019)
PURPOSE OF REVIEW: Beta-cell replacement is the best therapeutic option for patients with type 1 diabetes. Because of donor scarcity, more extended criteria donors are used for transplantation. Donation after circulatory death donors (DCD) are not commonly used for pancreas transplantation, because of the supposed higher risk of complications. This review gives an overview on the pathophysiology, risk factors, and outcome in DCD transplantation and discusses different preservation methods. RECENT FINDINGS: Studies on outcomes of DCD pancreata show similar results compared with those of donation after brain death (DBD), when accumulation of other risk factors is avoided. Hypothermic machine perfusion is shown to be a safe method to improve graft viability in experimental settings. SUMMARY: DCD should not be the sole reason to decline a pancreas for transplantation. Adequate donor selection and improved preservation techniques can lead to enhanced pancreas utilization and outcome.